The Relationship Between Psychological Capital and Perception of Organizational Support on Employee Performance - Etrya Loralita Mella Sary Sary; Nugraini Aprilia (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Organizations or companies cannot operate optimally without the presence of Human Resources (HR), who are tasked with producing, developing, and ensuring operational continuity. Organizational success can be achieved if employees not only complete their core tasks but also take an active role in activities such as collaborating, supporting each other, and providing input. Organizational Citizenship Behavior (OCB) refers to voluntary behavior intended to benefit others and involves factors such as psychological capital and perceived organizational support. The purpose of this study was to analyze the relationship between psychological capital and perceptions of organizational support in relation to OCB among employees of PT DK. This study employs quantitative research methods using both primary and secondary data. Primary data were collected through questionnaires administered to 70 respondents. Secondary data sources include information from journals, books, and data obtained from PT DK. The implications of this study provide an overview of psychological capital and perceptions of organizational support in relation to OCB. The results show a very significant relationship between psychological capital and perceptions of organizational support with organizational citizenship behavior. This indicates that individuals who possess psychological capital and perceive strong organizational support are more likely to exhibit OCB.